Risk and Return Comparison Analysis Between Gold, JKSE, and Property in Sumur Bandung, Bandung Wetan, and Coblong District in Long Term Investment - Soelaiman, Ratu Sitti Bashiira; Anggono, Achmad Herlanto (Journal of Business and Management, 2012)
Basically, the goal of investing is to maximize the investor’s return. There are three basic consideration in making an investment decision; they are return, risk, and the relationship level of risk and expected return. The longer time available to achieve financial objectives, the riskier instrument can be used in order to widening high return possibility and also allow us to accept the fluctuations of the value of our savings. The long-term investment products, such as property, gold, and stock are believed as the best choice in gaining high return as well as against the inflation. Gold is commonly regarded as a value and wealth protector, normally called ‘hedging’. The risk of investing in stocks is quite high, but until now the rate of return of the stocks is very much higher compared to the interest rate of savings and time deposits. Public interest on capital market investing continues to rise nowadays, can be seen from Jakarta Composite Index which illustrates the increasing number of members of exchanges, as well by changes in stock prices traded itself. Property prices keep increasing due to the ever-growing population. Properties can also provide passive income for the owner. Those three investment instruments are assumed potentially provide high return with a controllable risk for the investors.Key Word : Investment Instruments, Risk and Return, Gold, JKSE, Property